The Function of Language as an Adaptation Strategy for Javanese Transmigrants in Simpang Nangka Village, Selupu Rejang District, Bengkulu Province - Rusdi, Muhammad Usaid Ghifari; Kahanna, Mutia; Oktayanty, Yetty (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research is entitled "The Function of Language as an Adaptation Strategy forTransmigrants Java in Simpang Nangka Village, Selupu Rejang District, BengkuluProvince". This research aims to describe the adaptation process of Javanesetransmigrants in Indonesia Simpang Nangka Village and the function of language as anadaptation strategy for transmigrants Java. The theory used in this research is Bronislaw'sfunctionalism theory Malinowski The method used is a qualitative method, withtechniques collecting observation data, interviews and documentation.The results of this research explain that language functions as a strategyadaptation of Javanese transmigrants in Simpang Nangka Village. First of all bring it tohistory of transmigration to Simpang Nangka in 1964 through spontaneoustransmigration. From transmigration activities, the population in Simpang Nangka isdominated by two ethnicities namely the Javanese and the Rejang. While living inSimpang Nangka as a migrant The transmigrant population goes through severalprocesses to adapt there. As for Some of these processes are: Learning the Rejanglanguage, adaptation through agriculture,adaptation to social organizations, adaptationthrough kinship systems and so on.This research also explains the function of languageon related biological psychology human behavior and needs, then the function oflanguage in the economy, namely make it easier in the negotiation process and then thefunction of language in related politics voice through campaigns.